“I do have to represent the faith:” An Account of an Ecclesiological Problem When Teaching Philosophy in Ontario’s Catholic High Schools - McDonough, Graham P.; Bialystok, Lauren; Norris, Trevor; Pinto, Laura (Encounters in Theory and History of Education / Rencontres en Théorie et Histoire de l'Éducation / Encuentros en Teoría e Historia de la Educación)

(untitled) (Faculty of Education, Queen's University, 2022)
The Canadian province of Ontario introduced philosophy as a secondary school subject in 1995 (Pinto, McDonough, & Boyd, 2009). Since publicly-funded Catholic schools teach approximately 32% of all students in Ontario (Ontario Ministry of Education, 2022), the question arises regarding how teachers in those schools coordinate philosophy and Catholic teachings. This study employs a secondary analysis of interviews with six teachers from Ontario’s Catholic schools, and employs two of Avery Dulles’ (2002) conceptions of church (institution and mystical communion) to determine how they consider the choices available within their own tradition that could answer this question. Rather than looking only at the shortcomings of treating magisterial teaching as philosophy, this paper argues that there are also conceptual problems that these courses must address in order to improve their ecclesiological adequacy, and illustrates how an apparent null curriculum privileges the institutional ecclesiology.